Estudo da governança de TI interinstitucional em um ambiente de gestão de projetos de TI em órgãos públicos - Schaefer, Eduardo Dullius (2017)
The evolution of management and control in public organizations, in addition to initiatives of transparency and efficiency, were driven by the intense use of IT and provided the adoption of robust management tools, such as IT Governance (ITG). In an IT project management environment, governance can be shared through interinstitutional arrangements, depending of construction trust and collaboration process, and developing relationships between participating entities, creating an Interinstitutional IT Governance (I-ITG). The I-ITG is an incipient phenomenon that requires research to better understand the arrangements between organizations, mainly to understand the forces acting on the participants of this relationship and the complexity of involving independent cultures, processes, control mechanisms and management. Through the study in a state autarchy of Rio Grande do Sul (Brazil) and its corporate ICT service provider, the objective of this study is to analyze how the ITG is organized in each organization and to evaluate the interorganizational arrangements identified in the partnership, identifying how the Interinstitutional IT Governance can contribute to the management of public organizations. Issues involving the IT Governance model and mechanisms adopted in both the public organization and the partner in IT projects and what influences they may have on interinstitutional governance are investigated. For the conducting of this study was used the type of qualitative research, through exploratory approach, using a single case study and methods of semi-structured interview with previously determined script and collection of documents in the two researched institutions. Twelve interviews were conducted between December 15, 2016 and February 9, 2017 at the state autarchy and the company providing ICT services, through the strategic choice of participants according to their level of knowledge, experience and ability to contribute to the proposed objectives. Numerous documents related to the relationship between organizations were also collected, which are part of planning, corporate management and IT governance. The analysis of the collected material occurred through the content analysis method (BARDIN, 2011) and brought as main results the definition of the IT governance model of the institutions, besides investigating the evidences of the present ITG mechanisms. From the analysis of the theoretical reference and empirical study, comparing the ITG found in the organizations with previous researches, was possible to evaluate the level of adherence of the organizations with the minimum IT governance suggested for public institutions, demonstrating that the state autarchy presents a level of maturity in governance that is still incipient, but with several structured and organized initiatives, as well as a more intense work in order to develop maturity of the Project Management sphere (SAMBAMURTHY; ZMUD, 1999). Otherwise, the ICT service provider already demonstrates a greater degree of maturity in IT governance, with several mechanisms well structured and managed with periodic monitoring. It was also possible to suggest a conceptual model about the influences of I-ITG in the public IT project management environment, suggesting that the maturity of ITG mechanisms related to project management in each organization positively influences I-ITG and that relations formal, trustworthy and relationship are key to the success of the model. It can also be concluded that the process of negotiation, relationship and conflict resolution is of fundamental importance in interorganizational arrangements, more specifically in the IT Project Management environment, since the two public organizations investigated have a long-standing relationship and have already developed a relationship dynamics and a high level of confidence.